Assessment of Enamel Surface after Debonding of Different Types of Esthetic Brackets (An In Vitro Study) - Hasan, Ghaith M.; Al-Dabagh, Dhiaa J. N. (Journal of Baghdad College of Dentistry, 2016)
Background: Debonding orthodontic brackets and removal of residual bonding material from the enamel surface include critical steps that may cause enamel damage. The aim of the present study was to evaluate and compare the site of bond failure and enamel surface damage after debonding of three types of esthetic brackets (composite, ceramic, sapphire) bonded with light cure composite and resin-modified glass ionomer adhesive. Materials and methods: Seventy two maxillary premolars teeth were divided into three groups each group consisted of 24 teeth according to the type of brackets. Each group was subdivided into two subgroups (12 teeth for each) according to the bonding material that was used. After 7 days of bonding procedure, the brackets were debonded using specifically designed debonding device in which the brackets were debonded by a debonding pliers to simulate the actual clinical debonding procedure. Instron Universal testing was used to apply the debonding force on the debonding pliers which transferred to the bracket. The teeth and the brackets were examined with a 10X magnifying lens to evaluate the site of failure. After the removal of residual adhesive, stereomicroscope was used to evaluate enamel surface damage. Results: The most common type of bond failure was cohesive failure (Score II) in all esthetic brackets. While enamel cracks (scale I) were found to be the most type of enamel damage. Chi- square showed non-significant differences among different types of esthetic bracket bonded with same type of adhesive and between the same types of brackets (ceramic, sapphire) bonded with the two types of adhesive. On the other hand, there was significant difference between composite brackets subgroups bonded with the two adhesives. Conclusion: The bond failure mostly within the adhesive itself and higher enamel damage was resulted from mechanical debonding of these esthetic brackets.